(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Early osteogenesis and bone formation are key for treating bone injuries and bone diseases like osteoporosis. ?-Tricalcium phosphate (?-TCP) is a popular synthetic bone graft substitute with excellent osteoconductive properties and absorbability. Objective: To evaluate the histological and immunohistochemical changes by using ?-TCP on fracture healing in rabbits. Methods: Experimental study on animal model using 40 male adult albino rabbits, (Oryctolagus cuniculus). The control group included 20 rabbits and subdivided into 2 periods; two weeks and four weeks each one used 10 rabbits, and the treated group was also 20 in number and subdivided into 2 periods, two weeks and four weeks, each one used 10 rabbits. General anesthesia was induced with an intramuscular injection of xylazine 20 mg (0.2 ml/kg body weight) and ketamine HCl 50 mg (20 mg/kg body weight). The new bone formation length was measured histologically and by immunohistochemistry. Results: Histological findings for the bone healing process in the treated group with ?-TCP showed early bone marrow, trabecular bone, mineralization, and compact bone formation in comparison to the healing process in the control group. The comparative histomorphometric study showed a significant P value in comparison between 2 and 4 weeks the control group P value